Erbium-Doped Fibers Designed for Random Single-Frequency Lasers Operating in the Extended L-Band - Denis Lipatov; Alexey Abramov; Alexey Lobanov; Denis Burmistrov; Sergei Popov; Dmitry Ryakhovsky; Yuriy Chamorovskiy; Alexey Bazakutsa; Liudmila Iskhakova; Olga Egorova; Andrey Rybaltovsky (Photonics)
The paper presents the results of developing Er-doped optical fibers for creating random single-frequency lasers in the wavelength range of 1570–1610 nm. The possibility of broadening the luminescence band of Er3+ ions in silicate glasses in the long-wavelength region of the spectrum by introducing a high concentration of P2O5, as well as by additional doping with Sb2O3, is investigated. It is found that both approaches do not improve the dynamics of luminescence decay in the L-band. In addition, Er2O3-GeO2-Al2O3-SiO2 and Er2O3-GeO2-Al2O3-P2O5-SiO2 glasses were studied as the core material for L-band optical fibers. The developed fibers exhibited high photosensitivity and a high gain of 5 and 7.2 dB/m, respectively. In these fibers, homogeneous arrays of extended weakly reflecting Bragg gratings were recorded directly during the fiber drawing process. Samples of arrays 5 m long and with a narrow reflection maximum at ~1590 nm were used as the base for laser resonators. Narrow-band random laser generation in the wavelength region of 1590 nm was recorded for the first time. At a temperature of 295 K, the laser mode was strictly continuous wave and stable in terms of output power. The maximal power exceeded 16 mW with an efficiency of 16%.